HIPERTENSI, DIABETES MELLITUS, DAN OBESITAS SEBAGAI FAKTOR KOMORBIDITAS UTAMA TERHADAP MORTALITAS PASIEN COVID-19: SEBUAH STUDI LITERATUR - Luh Ade Dita Rahayu; Jannatul Cahya Admiyanti; Yumna Iftinan Khalda; Fatikha Rudia Ahda; Nur Feby Febiana Agistany; Sastraningsih Setiawati; Nabila Indah Shofiyanti; Cut Warnaini (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: COVID-19 patients with comorbid diseases have a higher mortality rate than patients without congenital diseases. The most common comorbids found in COVID-19 patients are diabetes mellitus, hypertension, and obesity. The prevalence of COVID-19 patients with diabetes mellitus reached 41.7%, hypertension reached 56.6%, and obesity reached 41.7%. Methods: The method used in this paper is literature review from various references and focused on the correlation of comorbid with the risk of death in COVID-19 patients. The references are being retrieved from NCBI and Google Scholar. Overall, 21 sources were used which were obtained from various data bases including PubMed, ScienceDirect, Researchgate, and WHO. Discussion: There is an increase in ACE-2 expression which causes a high susceptibility to SARS-CoV-2 infection on COVID-19 patient with hypertension. Impaired T-cell function and increased levels of interleukin-6 (IL-6) also play an important role in increasing the severity on COVID-19 patient with diabetes. Obesity can cause abnormalities in the secretion of cytokines, adipokines, and inferferon which will disrupt the immune system in the human body. Conclusion: The complex pathophysiological mechanisms of hypertension, diabetes mellitus, and obesity as comorbid in COVID-19 patients increase the severity and mortality risk.